Analysis of PjBL-STEAM implementation: Challenges for prospective teachers in developing android learning media - Lutfi, Muh. Khaedir; Kusumastuti, Fitri Anisa; Juana, Nadya Amalia; Nulhakim, Ade Lukman; Khomeni, Ayathollah; Lubis, Roslian; Santika, Eka (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2025)
Technological developments demand adaptation in the world of education, particularly in the integration of technology into mathematics learning. Prospective student teachers need to possess the competencies to create innovative learning media that are not only content-accurate but also visually and technologically engaging. This study aims to describe the implementation of the Project-Based Learning (PjBL) model with STEAM (Science, Technology, Engineering, Art, and Mathematics) content in producing Android-based mathematics learning media. The method used was descriptive qualitative through triangulation of observation data, discussions, and analysis of the output product. The results showed that PjBL facilitated students in practicing the engineering cycle of media creation. However, obstacles were encountered in the Technology and Mathematics elements, where students experienced difficulty transforming textbook content into the system logic of an Android application. Furthermore, technical barriers to mastery of tools (Technology) such as iSpring Suite were a major challenge. Nevertheless, this approach successfully encouraged students to integrate art elements into interface design and mathematical logic within a single, integrated product. It was concluded that the implementation of PjBL with a STEAM nuance effectively helped lecturers and students produce usable digital media products.